A comparative study of public primary education in the Philippines and Thailand - Kalayanakupt, Sadudee 1942- ([Quezon City s.n.], 1969)
The major purpose of the study is to determine, compare, and discuss the degree and extent of similarities and dissimilarities which may be discerned in the public primary educational systems of the Philippines and Thailand in terms of their historical background, aims and objectives, curriculum, time allotment, scope and content of each subject in each grade level, the teaching personnel, the organization and administration, and educational expenditures.
Thesis (M.Ed.)--University of the Philippines
Typescript (Carbon copy)
Keywords: Education, Primary -- Philippines; Education, Primary -- Thailand